Preferences Test of Brown Lady Bug Riptortus linearis Fabr. (Hemiptera : Alydidae) on Soybeans (Glycine max L.), Greenbeans (Vigna radiata L.) and Orok-orok (Crotolaria pallida Aiton.) in Screenhouse - ricky arbiansyah; Marheni Sembiring; Fatimah Zahara (Jurnal Agroekoteknologi, 2016)
The objective of the research was to know the preferences food of brown lady bug               (R. linearis) on the pod of soybeans, greenbeans and orok-orok in Screenhouse. This research was conducted in Pest Laboratory and Screenhouse of the Agriculture Faculty, University of Sumatera Utara (±25 m asl) from March until August 2015. This research was using non-factorial Randomized Block Design with 3 treatments, which are  soybeans, greenbeans and orok-orok with 9 replications. The result of this research showed that the pest R.linearis higher attacks on soybeans than greanbeans and orok-orok. The highest result in imago population of R. linearis was showed on soybeans (7.00), then on greenbeans (3.78), and orok-orok (1.22). The highest result in attacked pod percentage of R. linearis was showed on soybeans (81.88%), greenbeans (57.24%), and orok-orok (20.76%).